Virtual reality for teaching and learning in crime scene investigation. Issue 5 (September 2020) - Mayne, Richard; Green, Helen
Highlights: Virtual reality is an emerging technology with applications in teaching & learning. A bespoke virtual reality app was used for teaching crime scene investigation skills Our application supports learning and is enjoyable, cost-effective and accessible. Virtual reality will add greater breadth of experience to forensic science courses. Abstract: Simulated crime scene investigation is an essential component of forensic science education, but its implementation is costly and poses challenges to accessibility; offering personal investigations in higher education scenarios is often impossible. Virtual reality (VR) is an emerging technology which offers exciting prospects for teaching and learning, especially for imparting practical skills. We document here a multidisciplinary experimental study in which a bespoke VR crime scene app was designed and implemented, after which it was tested by both undergraduate student and staff/postgraduate student cohorts. Through both qualitative and quantitative analyses, we demonstrate that VR applications support learning of practical crime scene processing skills. VR-based practical sessions have the potential to add value to forensic science courses, through offering cost-effective practical experience, the ability to work in isolation and in a variety of different scenarios. Both user groups reported high levels of satisfaction with using the app and reports of adverse effects (motion sickness) were minimal. With reference to user feedback, we proceed to evaluate the scalability and development challenges associated with large-scale implementation of VR as an adjunct to forensic science education.